Analisis Faktor E-Purchasing Konstruksi Menggunakan RII dan Mixed Method - Irla Erdina Sari; Wahyudi P Utama; Khadavi (Institut Teknologi Garut, 2025)
This study aims to identify the driving and inhibiting factors in the implementation of e-purchasing in the selection of construction work providers. As an electronic-based procurement system, it is expected to improve efficiency, transparency, and accountability in the procurement process of goods and services. However, various obstacles are still found in its implementation. The results of the study show that the main driving factors consist of adequate information technology support, increased human resource capacity, and supportive regulations. Conversely, the inhibiting factors include unstable internet networks, a lack of socialization regarding the e-purchasing system, and a limited number of experts in this field. The research method used is quantitative descriptive with data analysis using the Relative Importance Index (RII). These results are expected to provide a basis for more effective electronic construction procurement policies.